Orthokeratology reshapes eyes to be less prolate and more symmetric. Issue 4 (August 2022) - Huang, Yingying; Li, Xue; Ding, Chenglu; Chen, Yunyun; Chen, Hao; Bao, Jinhua
Abstract: Purpose: This prospective study assessed the influence of wearing and then discontinuing orthokeratology (OK) lenses on retinal shape and peripheral refraction in myopic children. Methods: Fifty-eight myopic children (age 8–12 years) were equally divided into an OK group and a single vision spectacles (SVS) group. After 12 months of OK, it was discontinued for 1 month. Peripheral eye length (PEL), relative peripheral refraction (RPR), and corneal parameters were measured in the right eye on the nasal and temporal retinal sides at baseline, 6 months, and 12 months (13 months in OK group) visits. Results: In the SVS group, faster elongation of the temporal side PEL made the eyes more asymmetric and prolate, developing a temporal pointed shape. In the OK group, the nasal retinal side PEL grew faster, the nasal RPR developed less hyperopic defocus, and the eye shape became more symmetric and less prolate. The central cornea became thinner and flattened, while the peripheral cornea became steeper. Changes in corneal thickness, relative peripheral corneal power, and K-values were no significant differences for the OK and SVS groups at 12 months. Conclusions: The cornea reverted to be no difference with myopic children with SVS after 1 month discontinuation of OK. The retinal shape of SVS eyes became more asymmetric and prolate with myopia progression. OK remodelled retinal shape to be less asymmetric and less prolate.